Top-quark forward-backward asymmetry in Randall-Sundrum models beyond the leading order - Bauer, Martin; Westhoff, Susanne (Arxiv, 2010)
We calculate the ttbar forward-backward asymmetry, A_FB^t, in Randall-Sundrum (RS) models taking into account the dominant next-to-leading order (NLO) corrections in QCD. At Born level we include the exchange of Kaluza-Klein (KK) gluons and photons, the Z boson and its KK excitations, as well as the Higgs boson, whereas beyond the leading order (LO) we consider the interference of tree-level KK-gluon exchange with one-loop QCD box diagrams and the corresponding bremsstrahlungs corrections. We find that the strong suppression of LO effects, that arises due to the elementary nature and the mostly vector-like couplings of light quarks, is lifted at NLO after paying the price of an additional factor of alpha_s/(4 pi). In spite of this enhancement, the resulting RS corrections in A_FB^t remain marginal, leaving the predicted asymmetry SM-like. As our arguments are solely based on the smallness of the axial-vector couplings of light quarks to the strong sector, our findings are model-independent and apply to many scenarios of new physics that address the flavor problem via geometrical sequestering.
Gesehen am 10.01.2018